2022
DOI: 10.1155/2022/2600755
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Intraspinal Nerve Block Anesthesia on Intrapartum Fever and the Neonate

Abstract: Objective. To evaluate the impact of intraspinal nerve block anesthesia on intrapartum fever and the neonate. Methods. In this prospective study, between October 2019 and December 2020, 90 eligible primiparous women enrolled in the obstetrics and gynecology department of our hospital for delivery were recruited and assigned via the random number table method at a ratio of 1 : 1 to either an analgesic group given intraspinal nerve block anesthesia for labor or a nonanalgesic group without anesthesia for labor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Studies have also found that butorphanol can pass through the blood-brain and placental barriers and enter human milk [18]. Other researchers have observed that intravenous administration of conventional doses of butorphanol had no signi cant effect on neonates [19,20]. These studies have shown that butorphanol is safe for intravenous use, and the butorphanol nasal spray used in our study has a satisfactory analgesic effect, with a rapid onset of nasal administration, maintenance time of up to 4-5 hours, and low incidence of adverse reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also found that butorphanol can pass through the blood-brain and placental barriers and enter human milk [18]. Other researchers have observed that intravenous administration of conventional doses of butorphanol had no signi cant effect on neonates [19,20]. These studies have shown that butorphanol is safe for intravenous use, and the butorphanol nasal spray used in our study has a satisfactory analgesic effect, with a rapid onset of nasal administration, maintenance time of up to 4-5 hours, and low incidence of adverse reactions.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%